Long-term effectiveness of sphenopalatine ganglion stimulation for cluster headache - Jürgens, Tim P (Cephalalgia, 2016)
OBJECTIVES: The sphenopalatine ganglion (SPG) plays a pivotal role in cluster headache (CH) pathophysiology as the major efferent parasympathetic relay. We evaluated the long-term effectiveness of SPG stimulation in medically refractory, chronic CH patients. METHODS: Thirty-three patients were enrolled in an open-label follow-up study of the original Pathway CH-1 study, and participated through 24 months post-insertion of a microstimulator. Response to therapy was defined as acute effectiveness in ≥ 50% of attacks or a ≥ 50% reduction in attack frequency versus baseline. RESULTS: In total, 5956 attacks (180.5 ± 344.8, range 2–1581 per patient) were evaluated. At 24 months, 45% (n = 15) of patients were acute responders. Among acute responders, a total of 4340 attacks had been treated, and in 78% of these, effective therapy was achieved using only SPG stimulation (relief from moderate or greater pain or freedom from mild pain or greater). A frequency response was observed in 33% (n = 11) of patients with a mean reduction of attack frequency of 83% versus baseline. In total, 61% (20/33) of all patients were either acute or frequency responders or both. The majority maintained their therapeutic response through the 24-month evaluation. CONCLUSIONS: In the population of disabled, medically refractory chronic CH patients treated in this study, SPG stimulation is an effective acute therapy in 45% of patients, offering sustained effectiveness over 24 months of observation. In addition, a maintained, clinically relevant reduction of attack frequency was observed in a third of patients. These long-term data provide support for the use of SPG stimulation for disabled patients and should be considered after medical treatments fail, are not tolerated or are inconvenient for the patients.